Materials and construction technologies for sustainable development - Mohammad, Arif Kamal (Key engineering materials ;, 2016)
This special volume on 'Materials and Construction Technologies for Sustainable Development' contains Eleven chapters which address a wide range of issues pertaining to building materials with reference to energy efficiency. The volume will be of special interest to environmentally conscious engineers, producers of building materials, architects, building professional and it may also be useful to scientists and researchers.